Implicancia tributaria de la utilización de comprobantes de pago en operaciones no reales de la Empresa Grupo Arces SAC del distrito de Trujillo en el año 2014. - Licera Jimenez, Emily Sofía (2016)
This research "Tax Implications for the Use of Voucher No actual operations in the Arces Group Company INC. Trujillo District -2014 ", aims to establish the tax liability and criminal liability of the taxpayer. This research is aimed at analyzing the consequences that the use of receipts in no actual operations in the city of Trujillo, and to achieve this aim the analysis and interpretation of data collected from the proof of payment was made, accounting records, cross-references and other documents of Arces Group Company INC, using the techniques of observation and documentary analysis, allowing us to meet the objections by the misuse of tax credit of General Sales Tax and omission of income tax. And criminal liability for the use of receipts with false information, payment vouchers purchased or made by third parties, with the intention of misusing credit and tax expenditures. Through the results of observation and document analysis, the hypothesis was accepted: "The Tax Implications for the Use of Voucher in no actual operations in the Arces Group Company INC Trujillo District -2014 are the Criminal Responsibility and Tax.”The conclusions to which one can arrive in this research are the highest payment for unpaid taxes; general sales tax and income tax, default interest and with regard to criminal liability; custodial sentence of not less than 8 nor more than 12 years.